AN ERROR ANALYSIS OF RECOUNT TEXT TRANSLATION BY EFL PRE-SERVICE TEACHERS - Juniharma Dewi Dalimunthe (UIN Sumatera Utara, 2021)
This study aims to identify the errors and to describe the types of errors made by EFL Pre-service Teachers when translating recount texts from Indonesian to English. This research employed a qualitative descriptive method. The subject of this research is the 4th-semester student of the English Education Department, State Islamic University of North Sumatera. This research uses random sampling. The researcher only took data from 2 representatives from each class. The data were taken from translation tests and documentation. Based on the data, it is found that there are 38 and eleven types of errors made by the EFL Pre-service Teacher. The findings show that EFL Pre-service teachers make errors in terms of article error, plural noun error, punctuation error, phrase error, verb error, preposition error, misordering error, pronoun error, noun error, infinitive error, and spelling error. There is some process of the error occurred, namely: hesitates in using an appropriate article, doesn't pay much attention to grammar in the target language, misplaced punctuation, doesn't understand the rules of using the correct preposition and don't understand the use of pronouns in sentences. The causes of errors on EFL Pre-service Teachers in translating Recount Text are lack of motivation and Interlingual transfer/intralingual transfer.